Geotechnical teaching and research reaches fifty year milestone at TCD - O'Kelly, Brendan; Orr, Trevor (My University, 2009)
Brendan O?Kelly, Trevor Orr and Eric Farrell describe the development of geotechnical engineering, one of the youngest branches of civil engineering, and in particular the development of the curriculum and research laboratories in soil mechanics at the School of Engineering, Trinity College Dublin, from the initial stages just over 50 years ago, right up to the present day.
PUBLISHED
Keywords: Geotechnical teaching